Congenital anomalies of the IVC—embryological perspectives and clinical relevance - Ghandour, Abed; Partovi, Sasan; Karuppasamy, Karunakaravel; Rajiah, Prabhakar (Cardiovascular Diagnosis and Therapy; Vol 6, No 6 (December 29, 2016): Cardiovascular Diagnosis and Therapy (Advanced Venous Imaging and Image-guided Venous Interventions), 2016)
With the increased use of cross-sectional imaging, systemic venous anomalies are more frequently being recognized in asymptomatic patients. Accurate characterization of systemic venous anomalies plays a major role in the appropriate selection of a surgical approach or interventional procedure. In this article, we review common and uncommon inferior vena cava (IVC) anomalies. We describe the embryological basis and clinical implications of these anomalies, particularly from an interventional radiology perspective. We also discuss the complications and treatments of these anomalies.